2013
DOI: 10.1053/j.gastro.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Germline PTEN, BMPR1A, SMAD4, STK11, and ENG Mutations in Patients With Moderate-Load Colorectal Polyps

Abstract: BACKGROUND & AIMS Gastrointestinal polyposis is a common clinical problem, yet there is no consensus on how to best manage patients with moderate-load polyposis. Identifying genetic features of this disorder could improve management, and especially surveillance, of these patients. We sought to determine the prevalence of hamartomatous polyposis associated mutations in the susceptibility genes PTEN, BMPR1A, SMAD4, ENG, and STK11 in individuals with 5 or more gastrointestinal polyps, including at least 1 hamarto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
0
37
1
Order By: Relevance
“…There are varied gastrointestinal manifestations of PHTS as detailed in Table 1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], of which upper and lower gastrointestinal tract (GIT) polyposis is most common. PHTS patients are reported to have a wide spectrum of polyp histologies throughout their upper and lower GIT [3,4], with many having more than a single histology [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are varied gastrointestinal manifestations of PHTS as detailed in Table 1 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], of which upper and lower gastrointestinal tract (GIT) polyposis is most common. PHTS patients are reported to have a wide spectrum of polyp histologies throughout their upper and lower GIT [3,4], with many having more than a single histology [5].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal polyposis [2][3][4][5][6][7][8][9][10][11][12] Glycogenic acanthosis [2,8,11,13] Intestinal hyperplasia 14…”
Section: Gastrointestinal Feature Referencesmentioning
confidence: 99%
“…Histologically, there may be confusion with juvenile polyps [Jass, 2008]. Stromal ganglion cells are seen frequently [Jass, 2008], and may be so abundant that the appearance is that of ganglioneuromas [Trufant et al, 2012;Ngeow et al, 2013;Ponz de Leon et al, 2013], but lesions in which autonomic nerves are predominant, giving a ganglioneuroma-like appearance seem to be exceptional . Instead, true intestinal ganglioneuromas are found in neurofibromatosis type 1 and multiple endocrine neoplasia type 1 [Ledwidge et al, 2007].…”
Section: Pten Hamartoma Tumor Syndrome(s) (Phts)mentioning
confidence: 99%
“…Simultaneous occurrence of polyps of different histologies (including at least three of the following subtypes: adenoma, hamartoma, lipoma, ganglioneuroma-like, juvenile, and inflammatory polyps) has been found to be specifically associated with presence of PTEN mutations in a series of patients with multiple polyposis [Ngeow et al, 2013]. The number of polyps can range from none to innumerable, while their incidence is unknown; in a recent study 95% of in PTEN mutation carriers subjected to colonoscopy were found to have intestinal polyps [Heald et al, 2010].…”
Section: Pten Hamartoma Tumor Syndrome(s) (Phts)mentioning
confidence: 99%
See 1 more Smart Citation